Comparative study of fluoride and non-fluoride additives in high thermal conductive silicon nitride ceramics fabricated by spark plasma sintering and post-sintering heat treatment. Issue 18 (15th December 2018) - Yang, Chunping; Ye, Feng; Ma, Jie; Ding, Junjie; Zhang, Biao; Liu, Qiang; Zhang, Haoqian
Abstract: High thermal conductivity silicon nitride (Si3 N4 ) ceramics fabricated using fluoride and non-fluoride additives were comparatively investigated in this study for the first time. Three series of sintering aids, namely, MgF2 -Y2 O3, MgSiN2 -Y2 O3 and MgO-Y2 O3 were used to fabricate Si3 N4 ceramics by spark plasma sintering (SPS) at 1650 ℃ for 5 min and post-sintering heat treatment at 1900 ℃ for 4 h. Microstructure, thermal conductivity, and mechanical properties of Si3 N4 ceramics were comparative investigated. Results indicate that MgF2 as sintering additive for Si3 N4 ceramics is able to effectively reduce the temperature of liquid phase in SPS process. The proportion of large grains is about 34% in fluoride-doped sample, which is more than those samples using MgSiN2 and MgO as sintering aids (24% and 25%, respectively). Thermal conductivity of ceramics is 76, 64, and 60 Wm −1 K −1 for samples with MgF2, MgSiN2 and MgO, respectively. Fluoride-doped sample displayed good mechanical properties including bending strength (857.6 MPa), hardness (14.9 GPa), and fracture toughness (7.7 MPa m 1/2 ).